Dinosaur hunters - McMullan, Kate.; Jones, John, 1935- (New York : Random House, 1989)
Describes the work scientists do to find out more about these huge prehistoric animals.
4.0
3-6
Keywords: Paleontology -- Juvenile literature; Dinosaurs -- Juvenile literature; Dinosaurs; Paleontologists; Dinosaurs